2019
DOI: 10.4103/jfmpc.jfmpc_634_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of type 2 diabetes and their complications among home health care patients at Al-Kharj military industries corporation hospital

Abstract: Introduction:The diabetes mellitus type 2 is a result of hyperglycemia due to insulin resistance caused by insufficient secretion of insulin from the beta cells of pancreas. The detection and controlling of diabetes mellitus type 2 (DMT2) at primary health-care centers in Saudi Arabia is well justified and widely practiced. The knowledge and awareness of DMT2 patients should be increased through the determination of its prevalence which may decrease the rates of comorbidities.Methods:A questionnaire of 159 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…In various studies the prevalence of hypertension had wide range from 20% in newly diagnosed patients to 50% in others [6,22,23]. On the other hand, some studies reported the prevalence of hypertension and dyslipidemia ranged from 60 to 80% [1,4,16,17,24].…”
Section: Discussionmentioning
confidence: 99%
“…In various studies the prevalence of hypertension had wide range from 20% in newly diagnosed patients to 50% in others [6,22,23]. On the other hand, some studies reported the prevalence of hypertension and dyslipidemia ranged from 60 to 80% [1,4,16,17,24].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic patients with chronic health issues require extensive healthcare which can be fulfilled by providing the healthcare terms with sufficient, comprehensive, reliable, compactible & co-relating patients information across the different health sectors. 24 Thus study reported the prevalence of diabetes is more in the subjects of sedentary life-style, obese, Hypertensive & smokers. 25…”
Section: Factors Strongly Correlated With Co-morbid Dm and Htnmentioning
confidence: 92%
“…Ten out of 151 studies were included in the qualitative, [18][19][20][21][22][23][24][25][26][27] and 6 in the quantitative synthesis. [18,[20][21][22]25,27] A total of 141 (93.4%) studies were eliminated due to needing to meet the qualifying requirements. Figure 1 shows the excluded articles and the justifications for their exclusion.…”
Section: Flow Of Studiesmentioning
confidence: 99%
“…3A). Three studies [18,21,25] involving 3405 participants indicated that women had a slightly higher risk Bahijri et al (2016) [24] Jeddah Saudi and non-Saudi families 1420 Mean: 36.0 [25] Eastern province Aldossari et al (2018) [19] Al-Kharj Saudi adult males Albarakat and Guzu (2019) [21] Al Meo et al (2020) [22] Riyadh Cement industry workers of T2DM than men, although it was not statistically significant (OR = 1.39, 95% CI = 0.57-3.38) (Fig. 3B).…”
Section: Associations Of Age and Sex With T2dm Riskmentioning
confidence: 99%